A Dual-Wideband Double-Layer Magnetoelectric Dipole Antenna with a Modified Horned Reflector for 2G/3G/LTE Applications. (17th December 2013) - Feng, Botao; Hong, Weijun; Li, Shufang; An, Wenxing; Yin, Sixing
Abstract : A novel dual-wideband double-layer magnetoelectric dipole unidirectional antenna with a modified horned reflector for 2G/3G/LTE applications is proposed. Firstly, a double-layer electric dipole structure is presented to provide a dualwideband, whose folded lower layer mainly serves the lower frequency band while the inclined upper layer works for the upper frequency band. In addition, to reduce the size of the antenna and improve impedance matching, a new feeding structure designed with inverted U-shaped and tapered line is introduced. Finally, a modified horn-shaped reflector, instead of a ground plane, is employed to achieve stable and high gains. The antenna prototype can achieve a bandwidth of 24.4% (790 MHz–1010 MHz) with a stable gain of 7.2 ± 0.6 dBi for the lower band, and a bandwidth of 67.3% (1.38 GHz–2.78 GHz) with a gain of 7.5 ± 0.8 dBi for the upper band covering all the frequency bands for 2G/3G/LTE systems. To the best of our knowledge, it is the first double-layer magnetoelectric dipole antenna proposed. Compared with the existing ME dipole antennas, the proposed antenna, which is completely made of copper, can be easily fabricated at low cost and thus is practicable for 2G/3G/LTE applications.